PHOTONICS TECHNOLOGY AS A WAY FOR UPGRADING KEY TECHNICAL FEATURES OF RADIO-SIGNAL DELAY DEVICES - T. N. Bakhvalova; M. E. Belkin; I. V. Gladyshev; S. A. Kudzh; A. S. Sigov (Российский технологический журнал)
Based on the previous results for our investigations of various retarding materials for super-wide bandwidth long-term delay lines and shortcomings of the available fiberoptic delay links based on binary delay chain where semiconductor optical switches are used to switch in or out delay segments that are binary multiples of a minimum delay, the principles of optimization and design of next-generation fiber-optics radio-frequency delay devices are proposed. They include: (1) distributed structure of low-power emitters based on dense wavelength division multiplexing, (2) multicore optical fiber as retarding medium, (3) two-stage processing including optoelectronic repeater unit, and (4) optical recirculation time-delay circuit. Computer-aided simulation and experimental verification of the proposed principles have shown their feasibility, efficiency and the opportunity to improve significantly the energy consumption and weight-dimensional characteristics, to increase the maximum delay time up to the millisecond range with a step in the microsecond range, also to improve the quality and flexibility of the various apparatuses on basis of these devices.